Myroxylon pereirae (balsam of Peru): Still worth testing? - Guarneri, Fabrizio; Corazza, Monica; Stingeni, Luca; Patruno, Cataldo; Napolitano, Maddalena; Pigatto, Paolo D. M.; Gallo, Rosella; Cristaudo, Antonio; Romita, Paolo; Offidani, Annamaria; Schena, Donatella; Milanesi, Nicola; et al. (Contact dermatitis, 2021)
Background Because Myroxylon pereirae (MP), or balsam of Peru, is nowadays almost not used “as such,” and fragrance mix 1 (FM1) apparently is more sensitive in detecting fragrance allergy, the usefulness of testing MP in baseline series was recently questioned. Objectives Identification of the number of clinically relevant patch test reactions to MP not detected by FM1. Methods Retrospective analysis of 12 030 patients patch tested with MP and FM1 for contact dermatitis between January 2018 and December 2019 in 13 Italian dermatology clinics. Results Four hundred thirty‐nine patients (3.6%) had a positive patch test reaction to MP; 437 (3.6%) had a positive patch test reaction to FM1. Positive reactions to both MP and FM1 were observed in 119 subjects (1.0%), 310 (2.6%) reacted to MP only, 304 (2.5%) to FM1 only, 5 to MP and sorbitan sesquioleate (SSO), 9 to FM1 and SSO, and 5 to MP, FM1, and SSO. Single sensitizations were clinically relevant in 75.2% of cases for MP (62.9% current, 12.3% past) and 76.3% for FM1 (70.1% current, 6.2% past). Conclusions Based on our results, MP appears to be still worth testing along with FM1 in baseline series, because it allows detection of a remarkable number of fragrance allergies, often relevant, which would be otherwise missed.